Understanding acceptance of autonomous vehicles in Japan, UK, and Germany. Issue 1 (31st December 2022) - Taniguchi, Ayako; Enoch, Marcus; Theofilatos, Athanasios; Ieromonachou, Petros
ABSTRACT: This paper investigates the acceptance of Autonomous Vehicles (AVs) in Japan, the UK and Germany and speculates on the implications for policy and practice. Three on-line surveys of 3, 000 members of the public in total, which were conducted in January 2017 (Japan), March 2018 (UK) and November/December 2018 (Germany) were analysed using Principal Component Analysis and then with an Ordered Logit Model. It finds that acceptance of AVs was higher amongst people with higher expectations of the benefits of AVs, those with less knowledge of AVs, and those with lower perceptions of risk. It also finds frequent drivers and car passengers to be more accepting, but that socio-economic factors were mostly insignificant. Finally, there were significant cultural differences between the levels of acceptance between Japan (broadly positive), the UK (broadly neutral) and Germany (broadly negative). These findings suggest that AV promoters should raise (or at least maintain) expectations of AVs among the public; engage with the public to reverse the negative perception of AVs; address AV-generated fears; not bother targeting people by socio-economic group; target frequent car drivers and passengers with information about what AVs could do for them; and target countries where AVs already enjoy a positive image.